MEKANISME PEMBUKTIAN DAN PENYELESAIAN SENGKETA MALAPRAKTIK MEDIS OLEH MAJELIS KEHORMATAN DISIPLIN KEDOKTERAN INDONESIA (MKDKI) - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the mechanisms of proof and resolution of medical malpractice disputes by the Indonesian Medical Disciplinary Honour Council (MKDKI) through a literature review method. The results of the study indicate that the proof mechanisms in the MKDKI include stages of complaint, administrative verification, medical document examination, expert testimony, and disciplinary hearings that emphasise medical professional standards. MKDKI decisions hold a strategic position as initial evidence in subsequent legal proceedings, although their implementation still faces various challenges such as time constraints, incomplete medical documentation, and inadequate integration with law enforcement agencies. This study recommends strengthening regulations, enhancing human resource capacity, and digitising medical records to improve the effectiveness of the MKDKI's dispute resolution mechanism. As a result, the MKDKI is expected to provide fair and accountable legal protection for both patients and medical personnel in Indonesia.